Optical, electrochemical and photocatalytic properties of cobalt doped CsPbCl3 nanostructures: a one-pot synthesis approach - Aadil Ahmad Bhat (Nature Portfolio, 2021)
Abstract The present manuscript aims at the synthesis of cesium based halide perovskite nanostructures and the effect of cobalt doping on the structural, optical, lumnisent, charge storage and photocatalytic properties. In a very first attempt, we report the solvothermal synthesis of Co doped CsPbCl3 nanostructures under subcritical conditions. The structural features were demonstrated by X-ray diffraction (XRD) Surface morphology determined cubic shape of the synthesized particles. Doping is an excellent way to modify the properties of host material in particular to the electronic structure or optical properties. Incorporation of Co2+ ions in the perovskite structure tunes the optical properties of the nanostructures making this perovskite a visible light active material (Eg = 1.6 eV). This modification in the optical behaviour is the result of size effect, the crystallite size of the doped nanostructures increases with cobalt doping concentration. Photolumniscance (PL) study indicated that CsPbCl3 exhibited Blue emission. Thermogravametric analysis (TGA) revealed that the nanostructures are quite stable at elavated temperatures. The electrochemical performance depicts the pseudocapacative nature of the synthesized nanostructures and can used for charge storage devices. The charge storage capability showed direct proportionality with cobalt ion concentration. And Finally the photocatalytic performance of synthesized material shows superior catalytic ability degrading 90% of methylene blue (MB) dye in 180 min under visible light conditions.